The ground between : anthropologists engage philosophy - Das, Veena (Orient black swan, 2014)
Twelve leading anthropologists offer candid reflections on the influence of particular philosophers on their thought and ethnographic practices. They relate the philosophers to matters such as how to respond to the suffering of the other, how concepts arise in the give and take of everyday life, and how to be attuned to the world through the senses.